The dark fantastic : race and the imagination from Harry Potter to The hunger games - Thomas, Ebony Elizabeth, 1977- (Postmillennial pop., 2019)
The promise of escape draws people from all backgrounds to speculative fiction, but when people of color seek passageways into the fantastic the doors are often barred. This problem lies not only with children's publishing, but also with the television and film executives tasked with adapting these stories into a visual world. When characters of color do appear, they are often marginalized or subjected to violence, reinforcing for audiences that not all lives matter. In an engaging and provocative exploration of race in popular youth and young adult speculative fiction, Thomas considers four black girl protagonists from some popular stories of the early 21st century and reveals how these characters mirror the violence against black and brown people in our own world. -- adapted from jacket